The role of religion in the concepts of A. Toynbee and S. Huntington: common and different - Korshunova, Yanina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article examines the role of religion in the concepts of local civilisations by A. Toynbee and S. Huntington. The main ideas of the theory by A. Toynbee, where the significance of religion is enhanced during the period of the collapse of civilisations, are presented. As a bearer of the spiritual heritage, the church becomes a «chrysalis» that transfers energy from a dying civilisation to a daughter one. In the highest religions, which are able to appeal to the human soul, A. Toynbee sees the potential for achieving universal human unity aimed at achieving the common good. At the same time, history reveals a regression of the highest religions that have departed from their original state due to the imperfection of human nature. Achievement of unity will be possible when the followers of living higher religions (Christianity, Islam, Buddhism and Hinduism) realise the commonality of their history and abandon the struggle among themselves. In contrast, the idea of a conflict between carriers of different religious worldviews was developed by S. Huntington. He sees in religions a factor not of unification, but of division, since they not only draw resources from the spiritual potential of a person, but also endow his cultural identity and his mission with comprehensive unique symbols. Differences in world outlook and culture are fundamental, which makes the possibility of peaceful coexistence of representatives of different civilisations difficult to realise. In this way, if A. Toynbee recognises the idea of creating the inner unity of mankind on the basis of religion, then S. Huntington fundamentally denies it and asserts about impending conflicts on the «fault lines of civilisations».